Penerapan Kebijakan Asas Tunggal Pancasila dan Implikasinya terhadap Integrasi Nasional - Ilka Fajar Alief (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the history of the implementation of the Sole Principle of Pancasila during the New Order era. This policy was enacted in 1985 under the administration of President Suharto, requiring all political parties and mass organizations to adopt Pancasila as the sole ideological foundation of their organizations. The implementation of the sole principle was intended to strengthen national unity and prevent division caused by differing ideologies, particularly as an effort to counter the threats of communism and religious fundamentalism. The New Order period, which began in 1966, is known as an era of political stability and economic development, but it was also marked by the consolidation of government power through various repressive policies, including the enforcement of the sole principle. This research employs a descriptive qualitative method through a literature study approach. The findings indicate that the sole principle of Pancasila was used as a tool to control political life and to restrict ideologies deemed contrary to the state ideology. However, the policy also drew criticism for limiting freedom of expression and imposing ideological uniformity in organizational life in Indonesia.